Energy accumulator capsule rubber compound suitable for harsh use working conditions and preparation method of energy accumulator capsule rubber compound

By using high-temperature polymerized buty-chlorosulfonated polyethylene rubber in accumulator capsule rubber, and strengthening the material performance by grafting modified composite bentonite, the problem of insufficient rubber compounding rubber in the prior art is solved, and the performance of rubber compounding rubber is achieved. Higher tensile strength and durability, suitable for harsh working conditions.

CN119307023APending Publication Date: 2025-01-14GUANGDONG ZHONGYI HIGH-TECH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411571127.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The rubber mixing rubber used in existing accumulator capsules has low performance and cannot meet the long-term high-load and reliable working needs, especially under strict operating conditions.

Method used

High-temperature polymerized buty-chloroprene, chloroprene and chlorosulfonated polyethylene rubber are used as the main raw materials, and the performance of the material is enhanced by graft modification of composite bentonite, combined with a variety of active agents and plasticizers, to prepare suitable for harshness Rubber kneaded glue in working conditions. The method includes the step of preparing grafted modified composite bentonite, and the nano-sized dispersed structure is formed by treating tapioca starch and nano-bentonite to improve the mechanical properties and durability of the rubber.

Benefits of technology

It significantly improves the tensile strength, dynamic fatigue properties, ozone and thermal oxygen aging resistance of rubber, extends service life, broadens application scenarios, and improves product reliability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307023A_ABST
    Figure CN119307023A_ABST
Patent Text Reader

Abstract

The present invention discloses an energy accumulator capsule rubber compound suitable for harsh use conditions and a preparation method thereof, and relates to the technical field of rubber compounds, the energy accumulator capsule rubber compound comprises the following raw materials by weight: 100 parts of a rubber polymer, 60 parts of a reinforcing agent, 3-6 parts of a reinforcing agent, 5-10 parts of a plasticizer, 5-8 parts of an anti-aging agent, 10-15 parts of an active agent, 3-5 parts of an accelerator, and 10-30 parts of white carbon black. 1-3 parts of a peroxide vulcanizing agent and 4-6 parts of graft modified composite bentonite. The preparation method has the advantages that the product use environment adaptability, the market application scene and the use range are improved, the application reliability and safety are improved, excellent tensile strength and elongation at break are provided, the preparation efficiency and the yield of large-specification and special-specification products of the energy accumulator capsules are improved, and the mixing dispersion effect, the later-section forming preparation fluidity and the physical property stability are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber compound rubbers, and in particular to an accumulator bladder rubber compound rubber suitable for harsh working conditions and a preparation method thereof. Background Art

[0002] The accumulator capsule, also known as the accumulator bladder, is usually made of rubber and is an important component of the bladder accumulator. The accumulator capsule has the advantages of acid and alkali resistance, oil resistance, high strength, not easy to deform, flex resistance, and a wide operating temperature range. It is widely used in aerospace, automobile manufacturing, petrochemical, machine tools and other fields. The aerospace, automobile manufacturing, petrochemical, machine tools and other fields are the main demand ends for accumulator capsules. In the aerospace field, accumulator capsules have the advantages of good durability and impact resistance, and are mainly used in aircraft hydraulic systems; in the automotive manufacturing field, accumulator capsules can absorb the mechanical vibration of vehicles such as cranes, forklifts, and large buses, and are widely used in automotive suspension systems and drive systems.

[0003] In the prior art, the rubber compound used for accumulator capsules has low performance and cannot meet the requirements of long-term high load and reliable operation. To this end, we propose an accumulator capsule rubber compound suitable for harsh operating conditions and a preparation method to solve the above problems. Summary of the invention

[0004] The object of the present invention is to provide an accumulator bladder rubber compound suitable for severe operating conditions and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an accumulator capsule rubber compound suitable for harsh working conditions, wherein the raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 3-6 parts of reinforcing agent, 5-10 parts of plasticizer, 5-8 parts of antioxidant, 10-15 parts of activator, 3-5 parts of accelerator, 10-30 parts of white carbon black, 1-3 parts of peroxide vulcanizer, and 4-6 parts of grafted modified composite bentonite.

[0006] Furthermore, the method for preparing the grafted modified composite bentonite comprises the following steps:

[0007] First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry;

[0008] Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite;

[0009] The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid;

[0010] Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution;

[0011] The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the potassium persulfate solution is added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes, and then the acrylamide solution is added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

[0012] Furthermore, the mass fraction of the cassava starch slurry is 3-4%.

[0013] Furthermore, the mixing ratio of the nano-bentonite and the sulfuric acid solution is 20-28 g: 120 mL;

[0014] The mass fraction of the sulfuric acid solution is 8.5%;

[0015] The mass ratio of the acid-treated nano-bentonite and the cassava starch slurry is 30-35:100;

[0016] The mass fraction of potassium persulfate solution is 10%.

[0017] Furthermore, the inert gas is nitrogen;

[0018] The mass ratio of potassium persulfate solution and composite solution is 1:10;

[0019] The mass percentage of acrylamide solution is 25%;

[0020] The mixing mass ratio of the composite liquid and the acrylamide solution is 10:2-2.5.

[0021] Furthermore, the rubber polymer is one or a mixture of three of high temperature polymerized nitrile rubber, chloroprene rubber, and chlorosulfonated polyethylene rubber.

[0022] Furthermore, the reinforcing agent is oil furnace process N series carbon black, the plasticizer is polyester environmentally friendly plasticizer, the antioxidant is one or a mixture of DDA or ZTMI, and the activator is any one of stearic acid or zinc oxide.

[0023] Furthermore, the accelerator is one or a mixture of three of dibenzothiazole disulfide, tetramethylthiuram disulfide, and 4,4′-dimorpholine disulfide, the white carbon black is fumed white carbon black, and the peroxide vulcanizing agent is one or a mixture of three of dialkyl peroxide, diacyl peroxide, and peroxyester.

[0024] A method for preparing an accumulator bladder rubber compound suitable for harsh working conditions comprises the following steps:

[0025] S1. Set the temperature of the internal mixer, put the rubber polymer into the internal mixer for rubber breaking and kneading, add reinforcing agent, strengthening agent, plasticizer, antioxidant, activator, processing aid, white carbon black, peroxide vulcanizer, grafted modified composite bentonite in sequence, mix and knead, lift the hammer to exhaust and pressurize three times, and then discharge;

[0026] S2, lifting the material discharged from the mixer in S1 and putting it into the refining and tableting equipment for refining, tableting after refining, and preparing the A-stage rubber for parking and stacking;

[0027] S3, after the pile rubber in S2 is inspected and qualified, B refining is carried out, and the rubber is put into the closed kneading machine for kneading according to the volume, and the accelerator is added. After kneading and dispersion, the rubber is put into the filtering equipment for filtering.

[0028] S4, the rubber mixture B after filtering is transferred to the open refining and calendering equipment for calendering to prepare composite molding specification rubber sheets, and obtain the capsule rubber mixed rubber product that meets the requirements.

[0029] Furthermore, in step S1, the temperature of the internal mixer is set to 120-135°C, the rubber polymer is put into the internal mixer for breaking and kneading for 60 seconds, and mixed and kneaded for 10-15 minutes. During this period, the hammer is lifted three times at 105°C, 115°C, and 125°C for exhaust and pressurization, and then the material is discharged at 135°C.

[0030] Further, in step S2, the tablets are pressed after refining for 5-8 minutes;

[0031] Furthermore, in step S3, the mixture is put into a closed kneading machine in sequence according to the volume for kneading for 30 seconds.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention uses high-temperature polymerized nitrile rubber as the main raw material, combined with chloroprene and chlorosulfonated polyethylene rubber or elastomer, while ensuring excellent tensile strength, dynamic fatigue and other physical properties, taking into account and improving the material's aging performance such as ozone resistance, thermal oxygen resistance and the tolerance range of the medium used, thereby improving the product's adaptability to the use environment, market application scenarios and use range, and improving application reliability and safety.

[0034] The ultra-high molecular weight polyester plasticizer used in the formula of the present invention takes into account the plasticizing effects of the above three rubber polymers, and provides excellent tensile strength and elongation at break while ensuring that its medium tolerance and aging performance meet a wide range of application scenarios, thereby improving the production efficiency and yield rate of large-size and special-size accumulator capsule products.

[0035] The formula of the present invention adopts a combination of multiple active agents, and the rubber polymer, reinforcing agent and surfactant are balanced to ensure the mixing and dispersing effect and the stability of the fluidity and physical properties of the post-molding preparation.

[0036] The present invention is based on nano-bentonite to prepare grafted modified composite bentonite. Since nano-montmorillonite has a layered silicate structure, its basic structural unit is formed by a layer of aluminum oxide octahedron sandwiched between two silicon oxide tetrahedrons, and there are exchangeable cations between the layers. This structure makes the nano-bentonite have a large specific surface area and interlayer space. After the nano-bentonite is prepared into a grafted modified composite bentonite and introduced, in the rubber processing process, the grafted modified composite bentonite can form a nano-scale dispersion effect with the rubber molecular chain through the intercalation or exfoliation effect, and this dispersion effect can effectively enhance the nano- The interfacial bonding force between bentonite and rubber matrix improves the mechanical properties of rubber; the various active groups on the surface of grafted modified composite bentonite can undergo physical or chemical adsorption with rubber molecular chains to form crosslinking points, which effectively restrict the movement of rubber molecular chains, improve the tensile strength and stability of rubber, and can inhibit the generation and subsequent development of cracks in the process of rubber cracking; the layered structure of grafted modified composite bentonite forms a continuous barrier layer in rubber, which helps to improve the air tightness, oil resistance, flame retardancy and other barrier properties of rubber. The presence of grafted modified composite bentonite can also improve the thermal stability of rubber and delay the aging process of rubber at high temperatures, thereby broadening its application field and increasing its service life.

[0037] Instruction Manual

[0038] Figure 1 It is a statistical diagram of the tensile strength of each group of samples in the embodiment and the comparative example. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The present invention provides a technical solution: an accumulator capsule rubber compound suitable for harsh working conditions, wherein the raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 3-6 parts of reinforcing agent, 5-10 parts of plasticizer, 5-8 parts of antioxidant, 10-15 parts of activating agent, 3-5 parts of accelerator, 10-30 parts of white carbon black, 1-3 parts of peroxide vulcanizing agent, and 4-6 parts of grafted modified composite bentonite; the rubber polymer is high temperature polymerized nitrile rubber, chloroprene rubber, chlorosulfonated polyethylene rubber, etc. the reinforcing agent is oil furnace process N series carbon black, the plasticizer is polyester environmentally friendly plasticizer, the antioxidant is one of DDA or ZTMI or a mixture of two of them, the activator is any one of stearic acid or zinc oxide, the accelerator is one of dibenzothiazole disulfide, tetramethylthiuram disulfide, 4,4'-dimorpholine disulfide or a mixture of three of them, the white carbon black is fumed white carbon black, and the peroxide vulcanizing agent is one of dialkyl peroxide, diacyl peroxide and peroxy ester or a mixture of three of them.

[0041] The following are specific embodiments:

[0042] Example 1

[0043] The raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 3 parts of reinforcing agent, 7 parts of plasticizer, 6 parts of antioxidant, 12 parts of activator, 3 parts of accelerator, 20 parts of white carbon black, 2 parts of peroxide vulcanizing agent and 4 parts of grafted modified composite bentonite.

[0044] The preparation method of graft modified composite bentonite comprises the following steps:

[0045] First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry;

[0046] Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite;

[0047] The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid;

[0048] Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution;

[0049] The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Nitrogen is then introduced into the reactor to exhaust the air in the reactor. Potassium persulfate solution is then added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes. Acrylamide solution is then added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

[0050] The mass fraction of cassava starch slurry is 3%.

[0051] The mixing ratio of nano-bentonite and sulfuric acid solution is 20g:120mL;

[0052] The mass fraction of the sulfuric acid solution is 8.5%;

[0053] The mass ratio of the acid-treated nano-bentonite and cassava starch slurry is 30:100;

[0054] The mass fraction of potassium persulfate solution is 10%.

[0055] The mass ratio of potassium persulfate solution and composite solution is 1:10;

[0056] The mass percentage of acrylamide solution is 25%;

[0057] The mixing mass ratio of the composite solution and the acrylamide solution is 10:2.

[0058] Example 2

[0059] The raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 4 parts of reinforcing agent, 5 parts of plasticizer, 5 parts of antioxidant, 10 parts of activator, 3 parts of accelerator, 30 parts of white carbon black, 3 parts of peroxide vulcanizing agent and 5 parts of grafted modified composite bentonite.

[0060] The preparation method of graft modified composite bentonite comprises the following steps:

[0061] First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry;

[0062] Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite;

[0063] The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid;

[0064] Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution;

[0065] The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Nitrogen is then introduced into the reactor to exhaust the air in the reactor. Potassium persulfate solution is then added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes. Acrylamide solution is then added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

[0066] The mass fraction of cassava starch slurry is 3.5%.

[0067] The mixing ratio of nano-bentonite and sulfuric acid solution is 22g:120mL;

[0068] The mass fraction of the sulfuric acid solution is 8.5%;

[0069] The mass ratio of the acid-treated nano-bentonite and cassava starch slurry was 31:100;

[0070] The mass fraction of potassium persulfate solution is 10%.

[0071] The mass ratio of potassium persulfate solution and composite solution is 1:10;

[0072] The mass percentage of acrylamide solution is 25%;

[0073] The mixing mass ratio of the composite liquid and the acrylamide solution is 10:2.3.

[0074] Example 3

[0075] The raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 5 parts of reinforcing agent, 10 parts of plasticizer, 8 parts of antioxidant, 15 parts of activator, 5 parts of accelerator, 10 parts of white carbon black, 1 part of peroxide vulcanizing agent and 4.5 parts of grafted modified composite bentonite.

[0076] The preparation method of graft modified composite bentonite comprises the following steps:

[0077] First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry;

[0078] Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite;

[0079] The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid;

[0080] Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution;

[0081] The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Nitrogen is then introduced into the reactor to exhaust the air in the reactor. Potassium persulfate solution is then added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes. Acrylamide solution is then added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

[0082] The mass fraction of cassava starch slurry is 3.6%.

[0083] The mixing ratio of nano-bentonite and sulfuric acid solution is 25g:120mL;

[0084] The mass fraction of the sulfuric acid solution is 8.5%;

[0085] The mass ratio of the acid-treated nano-bentonite and cassava starch slurry was 33:100;

[0086] The mass fraction of potassium persulfate solution is 10%.

[0087] The mass ratio of potassium persulfate solution and composite solution is 1:10;

[0088] The mass percentage of acrylamide solution is 25%;

[0089] The mixing mass ratio of the composite liquid and the acrylamide solution is 10:2.3.

[0090] Example 4

[0091] The raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 5 parts of reinforcing agent, 5 parts of plasticizer, 5 parts of antioxidant, 10 parts of activator, 5 parts of accelerator, 15 parts of white carbon black, 3 parts of peroxide vulcanizing agent and 6 parts of grafted modified composite bentonite.

[0092] The preparation method of graft modified composite bentonite comprises the following steps:

[0093] First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry;

[0094] Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite;

[0095] The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid;

[0096] Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution;

[0097] The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Nitrogen is then introduced into the reactor to exhaust the air in the reactor. Potassium persulfate solution is then added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes. Acrylamide solution is then added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

[0098] The mass fraction of cassava starch slurry is 4%.

[0099] The mixing ratio of nano-bentonite and sulfuric acid solution is 28g:120mL;

[0100] The mass fraction of the sulfuric acid solution is 8.5%;

[0101] The mass ratio of the acid-treated nano-bentonite and cassava starch slurry is 35:100;

[0102] The mass fraction of potassium persulfate solution is 10%.

[0103] The mass ratio of potassium persulfate solution and composite solution is 1:10;

[0104] The mass percentage of acrylamide solution is 25%;

[0105] The mixing mass ratio of the composite liquid and the acrylamide solution is 10:2.5.

[0106] The above embodiment preparation method comprises:

[0107] A method for preparing an accumulator bladder rubber compound suitable for harsh working conditions comprises the following steps:

[0108] S1. The temperature of the internal mixer is set to 120°C. The rubber polymer is put into the internal mixer for breaking and kneading for 60 seconds. The reinforcing agent, the strengthening agent, the plasticizer, the antioxidant, the activator, the processing aid, the white carbon black, the peroxide curing agent, and the grafted modified composite bentonite are added in sequence. The mixing and kneading are carried out for 10 minutes. During the mixing, the hammer is lifted for exhaust and pressurization at 105°C, 115°C, and 125°C for three times, and then the material is discharged at 135°C.

[0109] S2, lifting the material discharged from the mixer in S1 and putting it into the refining and tableting equipment for refining, tableting after refining, and preparing the A-stage rubber for parking and stacking; tableting after refining for 5 minutes;

[0110] S3, after the pile rubber in S2 is inspected and qualified, B refining is carried out, and the rubber is put into the closed kneading machine in turn according to the volume for kneading for 30 seconds, and the accelerator is added. After kneading and dispersion, the rubber is put into the filtering equipment for filtering.

[0111] S4, the rubber mixture B after filtering is transferred to the open refining and calendering equipment for calendering to prepare composite molding specification rubber sheets, and obtain the capsule rubber mixed rubber product that meets the requirements.

[0112] Comparative Example 1:

[0113] The difference from Example 1 is that no grafted modified composite bentonite is added, and the rest of the technical solutions remain unchanged.

[0114] Comparative Example 2:

[0115] The difference from Example 1 is that the grafted modified composite bentonite is replaced by an equal amount of untreated bentonite, and the rest of the technical scheme remains unchanged.

[0116] Table 1 shows the names and proportions of the raw materials for rubber compounding

[0117]

[0118] The performance of the samples of the embodiment and the comparative example was tested, as shown in Table 2:

[0119] Table 2 shows the performance parameters of the rubber compounds prepared in Examples 1-4

[0120]

[0121]

[0122] As can be seen from Table 2, the hardness is between 70-80ShoreA, the tensile strength is ≥15MPa, the elongation at break is ≥300%, the ozone aging resistance is 2c (the meaning of 2c is represented by standard GB / T 11206-2019), the heat oxygen aging resistance (100℃×72h), the tensile strength change rate is within ±10%, and the elongation change rate is within ±10%.

[0123] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An accumulator bladder rubber compound suitable for severe working conditions, characterized in that: The raw materials include, by weight: 100 parts of rubber polymer, 60 parts of reinforcing agent, 3-6 parts of reinforcing agent, 5-10 parts of plasticizer, 5-8 parts of antioxidant, 10-15 parts of activator, 3-5 parts of accelerator, 10-30 parts of white carbon black, 1-3 parts of peroxide vulcanizing agent and 4-6 parts of grafted modified composite bentonite.

2. The accumulator bladder rubber compound suitable for severe working conditions according to claim 1, characterized in that: The method for preparing the grafted modified composite bentonite comprises the following steps: First, cassava starch is added into water, and stirred to mix evenly to obtain cassava starch slurry; Adding nano-bentonite to sulfuric acid solution, adjusting the temperature to 80°C, keeping the temperature and stirring for 40 minutes, and then filtering, washing and drying to obtain acid-treated nano-bentonite; The obtained acid-treated nano-bentonite was added to the cassava starch slurry, and stirred at a speed of 500 r / min for 30 min to obtain a composite liquid; Add potassium persulfate to water, stir and mix evenly to obtain a potassium persulfate solution; The composite liquid is added to the reactor, and then the temperature in the reactor is adjusted to 60°C and kept warm for 30 minutes. Then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the potassium persulfate solution is added dropwise to the reactor while stirring. The potassium persulfate solution is added dropwise within 30 minutes, and then the acrylamide solution is added and stirring is continued for 1 hour. After discharging, cooling, drying to constant weight, crushing, and passing through a 500-mesh sieve, the product is obtained.

3. The accumulator bladder rubber compound suitable for severe use conditions according to claim 2, characterized in that: The mass fraction of the cassava starch slurry is 3-4%.

4. The accumulator bladder rubber compound suitable for severe use conditions according to claim 1, characterized in that: The mixing ratio of the nano-bentonite and the sulfuric acid solution is 20-28 g: 120 mL; The mass fraction of the sulfuric acid solution is 8.5%; The mass ratio of the acid-treated nano-bentonite and the cassava starch slurry is 30-35:100; The mass fraction of potassium persulfate solution is 10%.

5. The accumulator bladder rubber compound suitable for severe use conditions according to claim 1, characterized in that: The inert gas is nitrogen; The mass ratio of potassium persulfate solution and composite solution is 1:10; The mass percentage of acrylamide solution is 25%; The mixing mass ratio of the composite liquid and the acrylamide solution is 10:2-2.

5.

6. The accumulator bladder rubber compound suitable for severe use conditions according to claim 1, characterized in that: The rubber polymer is one or a mixture of three of high temperature polymerized nitrile rubber, chloroprene rubber and chlorosulfonated polyethylene rubber.

7. The accumulator bladder rubber compound suitable for severe use conditions according to claim 1, characterized in that: The reinforcing agent is oil furnace process N series carbon black, the plasticizer is polyester environmentally friendly plasticizer, the antioxidant is one of DDA or ZTMI or a mixture of the two, and the activator is any one of stearic acid or zinc oxide.

8. The accumulator bladder rubber compound suitable for severe use conditions according to claim 1, characterized in that: The accelerator is one of dibenzothiazole disulfide, tetramethylthiuram disulfide, 4,4'-dimorpholine disulfide or a mixture of three thereof; the white carbon black is fumed white carbon black; and the peroxide vulcanizing agent is one of dialkyl peroxide, diacyl peroxide and peroxyester or a mixture of three thereof.

9. A method for preparing an accumulator bladder rubber compound suitable for severe use conditions based on any one of claims 1 to 8, characterized in that: The specific steps include: S1. Set the temperature of the internal mixer, put the rubber polymer into the internal mixer for rubber breaking and kneading, add reinforcing agent, strengthening agent, plasticizer, antioxidant, activator, processing aid, white carbon black, peroxide vulcanizer, grafted modified composite bentonite in sequence, mix and knead, lift the hammer to exhaust and pressurize three times, and then discharge; S2, lifting the material discharged from the mixer in S1 and putting it into the refining and tableting equipment for refining, tableting after refining, and preparing the A-stage rubber for parking and stacking; S3, after the pile rubber in S2 is inspected and qualified, B refining is carried out, and the rubber is put into a closed kneading machine for kneading according to the volume, and a promoter is added. After kneading and dispersion, the rubber is put into filtering equipment for filtering. S4, the rubber mixture B after filtering is transferred to the open refining and calendering equipment for calendering to prepare composite molding specification rubber sheets, and obtain the capsule rubber mixed rubber product that meets the requirements.

10. The method for preparing a rubber compound for accumulator bladders suitable for harsh working conditions according to claim 9, characterized in that: In step S1, the temperature of the internal mixer is set to 120-135°C, the rubber polymer is put into the internal mixer for breaking and kneading for 60 seconds, and mixed and kneaded for 10-15 minutes, during which the hammer is lifted three times at 105°C, 115°C, and 125°C for exhaust and pressurization, and then the material is discharged at 135°C; In step S2, the tablets are pressed after refining for 5-8 minutes; In step S3, the materials are sequentially put into the closed kneading machine according to the volume and the kneading time is 30 seconds.